Lead and cadmium removal from wastewater using eco-friendly biochar adsorbent derived from rice husk, wheat straw, and corncob - Amen, R. (Elsevier Ltd, 2020)
Cleaner and sustainable water production lead to the development of environmentally friendly adsorbent materials for energy-efficient, cost-effective, and cleaner water production. In this study, the biochar derived from the rice husk, wheat straw, and corncob has been used for the adsorptive removal of heavy metals, including the lead (Pb+2) and cadmium (Cd+2). The synthesised biochar was characterised by a different structural and analytical approach. The characterisation of biochar revealed the existence of the combined redox, i.e. reductive and oxidative surface functional groups along with some inert functional groups which play a significant role in donating or accepting an electron to degrade the pollutants in the wastewater. The biochar synthesised in this study was found to be amorphous, and some negligible disorders and defects have been observed in the structure of biochar. The biochar has been highly stable under harsh thermal conditions by sustaining significant weight over a temperature of 700 âÂ°C and also be hygroscopic. The biochar rice husk, wheat straw, and corncob demonstrated the lead (Pb+2) adsorption capacity of 96.41, 95.38, and 96.92, while for cadmium (Cd+2), the uptake capacity was found to be 94.73, 93.68, and 95.78. The reported biochar is a cleaner, environmentally friendly, economical, and sustainable alternative to conventional adsorbent materials. Â© 2020 The Author(s)